THE DIFFERENCES CATCHING DRIFT BOTTOM GILLNET IN THE AFTERNOON AND NIGHT AT TELUK PAMBANG VILLAGE OF BANTAN SUBDISTRICT OF BENGKALIS DISTRICT OF RIAU PROVINCE - Khairul Fadhli; Pareng Rengi; Syaifuddin Syaifuddin (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted on March-April 2018  in Teluk Pambang village of Bantan Subdistrict of Bengkalis District of Riau Province. The purpose of this study was to determined differences drift gillnet catches according of day to the operational. This resech used a survey method. The night catches bigger then day light catches in respectively total catches is 366 kg (77 fish) and 230,9 kg (51 fish).The calculation of t test there are differences in the bottom gillnet catches the day light and at night. Keyword : Bottom gillnet, catches in afternoon and at night